An inverted‐F antenna design for WLAN/WiMAX dual‐network applications. Issue 5 (20th December 2013) - Sim, C. Y. D.; Lai, Y. N.
ABSTRACT This study designed a compact size (45 mm × 9 mm × 1.6 mm) stand‐alone dualband inverted‐F antenna (IFA) printed on a low‐cost FR4 substrate for dual‐network WLAN (2.4/5.2/5.8 GHz) and WiMAX (2.5/3.5/5.5 GHz) operating bands. To achieve broad 10‐dB bandwidth of more than 45% and 31% for the lower and upper operating bands, respectively, the techniques of shorting the open‐end of the microstrip feed line to the driven monopole and loading a C‐shaped parasitic element with dissimilar arm lengths into the opposite side of the IFA were introduced. Further experimental results also show that the proposed IFA have efficiencies of more than 60% throughout the bands of interest. © 2013 Wiley Periodicals, Inc. Int J RF and Microwave CAE 24:523–528, 2014.